1977
DOI: 10.1002/bit.260190907
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon uptake in hydrocarbon fermentations

Abstract: Candida lipolytica (strain ATCC 8662) was grown on a simple defined medium with n-hexadecane as the main carbon source under batch fementation conditions. The relative importance of the cells growing in the aqueous phase on the overall kinetics was studied. The effect of interfacial tension, unoccupied interfacial area, and pseudosolubility on the specific growth was also studied. Results are presented and discussed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Studies focused on the kinetics of growth of yeasts on n-alkanes were conducted in the seventies and models were proposed to account for the complex kinetic patterns observed (Blanch & Einsele, 1973 ;Erickson et al, , 1970Gutierrez & Erickson, 1977 ;Moo-Young & Shimizu, 1971 ;Verkooyen & Rietma, 1980a, b ;Yoshida & Yamane, 1974). However, with other alkane-degrading micro-organisms, the interest was essentially oriented towards the production of biosurfactants and kinetic studies are scarce.…”
Section: Whatever the Mechanisms Involved A Point Which Ismentioning
confidence: 99%
“…Studies focused on the kinetics of growth of yeasts on n-alkanes were conducted in the seventies and models were proposed to account for the complex kinetic patterns observed (Blanch & Einsele, 1973 ;Erickson et al, , 1970Gutierrez & Erickson, 1977 ;Moo-Young & Shimizu, 1971 ;Verkooyen & Rietma, 1980a, b ;Yoshida & Yamane, 1974). However, with other alkane-degrading micro-organisms, the interest was essentially oriented towards the production of biosurfactants and kinetic studies are scarce.…”
Section: Whatever the Mechanisms Involved A Point Which Ismentioning
confidence: 99%
“…Specifically, in the presence of casein and/or olive oil, Nacetylglucosamine and serum Y. lipolytica transitions from yeast to mycelial forms (Ota et al, 1984;Guevara-Olvera et al, 1993;Zinjarde et al, 1998;Kim et al, 2000;Pérez-Campo & Domínguez, 2001;Ruiz-Herrera & Sentandreu, 2002;Szabo & Štofaníková, 2002;Kawasse et al, 2003). The opposite phenomenon has been observed when glucose or alkanes are used as carbon source or when cultivated at low pH (Gutierrez & Erickson, 1977;Rodríguez & Domínguez, 1984;Guevara-Olvera et al, 1993;Zinjarde et al, 1997Zinjarde et al, , 1998Szabo & Štofaníková, 2002). Significant progress has recently been made in identifying genes that play a crucial role in the dimorphism of Y. lipolytica (genes involved in the mitogen-activated protein kinase and protein kinase A pathways, Rho family, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Emulsification which increases the surface area between two immiscible phases, results in small oil drops in water. It is generally concluded that microorganisms growing on water-insoluble hydrocarbons benefit from the presence of a surfactant (6,8,13). Biosurfactants are usually complex lipids, with more chemically complicated structures than synthetic surfactants.…”
mentioning
confidence: 99%